Deciphering the genomic insights into the coexistence of congenital scoliosis and congenital anomalies of the kidney and urinary tract - Wang, Haojun; Wen, Wen; Yao, Mingxi; Yang, Tongwang; Chen, Dongshan; Wang, Wei (Frontiers in Genetics, 2024)
Congenital scoliosis and congenital anomalies of the kidney and urinary tract are distinct genetic disorders with differing clinical manifestations. Clinically, their coexistence is not rare, but the etiologies of these complex diseases remain largely unknown, especially their shared genetic basis.We sequenced the genomes of 40 individuals diagnosed with both CS and CAKUT, alongside 2,764 controls from a Chinese Han population cohort. Our analyses encompassed gene-based and pathwaybased weighted rare variant association tests, complemented by copy number variant association analyses, aiming to unravel the shared genomic etiology underlying these congenital conditions.Gene-based analysis identified PTPN11 as a pivotal gene influencing both skeletal and urinary system development (P = 1.95E-21), participating in metabolic pathways, especially the MAPK/ERK pathway known to regulate skeletal and urinary system development. Pathway-based enrichment showed a significant signal in the MAPK/ERK pathway (P = 3E-04), reinforcing the potential role of PTPN11 and MAPK/ERK pathway in both conditions. Additionally, CNV analysis pinpointed IGFLR1 haploinsufficiency as a potential influential factor in the combined CS-CAKUT phenotypic spectrum.This study enriches our understanding of the intricate genomic interplay underlying congenital scoliosis and kidney and urinary tract anomalies, emphasizing the shared genetic foundations between these two disorders.